2021
DOI: 10.3906/sag-2009-76
|View full text |Cite
|
Sign up to set email alerts
|

Family-centeredness of services for young children with Down syndrome: an observational study from Turkey

Abstract: Background/aim: Physicians require information on the family centeredness of services for children with Down syndrome, one of the most frequently encountered disabilities in childhood. We aimed to determine the family-centeredness of services for young children with Down syndrome and using a bioecological theory framework we hypothesized that child, family and service-related factors would be associated with such services. Materials and methods: In a cross-sectional design, children with Down syndrome seen at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
2
7
1
Order By: Relevance
“…This along with This, along with content validity for locally translated versions of the MPOC-20, has been established in other LMICs, such as Brazil, Jordan, and Turkey, and provides indirect evidence for the content validity of the Hindi MPOC-20. 12,14,22 Notably, despite including a selected population of families with higher education in India, the MPOC-20 could not be used as a self-administered tool as has been the case in Western countries. 27 A large proportion of caregivers were not able to self-administer the MPOC-20 items and needed assistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This along with This, along with content validity for locally translated versions of the MPOC-20, has been established in other LMICs, such as Brazil, Jordan, and Turkey, and provides indirect evidence for the content validity of the Hindi MPOC-20. 12,14,22 Notably, despite including a selected population of families with higher education in India, the MPOC-20 could not be used as a self-administered tool as has been the case in Western countries. 27 A large proportion of caregivers were not able to self-administer the MPOC-20 items and needed assistance.…”
Section: Discussionmentioning
confidence: 99%
“…This along with This, along with content validity for locally translated versions of the MPOC-20, has been established in other LMICs, such as Brazil, Jordan, and Turkey, and provides indirect evidence for the content validity of the Hindi MPOC-20. 12,14,22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of FCC may be influenced by many factors related to the child, family, or environment. Previous research has shown that the extent of the family-centeredness of care is associated with the parents' educational level and family income/socioeconomical status, but not related to a child's secondary impairments [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…FCC is an approach to health care that emphasizes partnership with the parents in the care of their child. This approach encourages the family's active participation in recognizing the requirements and key concerns of their child's care, and subsequently strategizing interventions tailored to those needs [10,[12][13][14][15][16]. The basic principles of FCC include treating families with respect; parent-professional partnerships; effective communication; and providing treatment choices to enable families to make informed decisions [12][13][14]17,18].…”
Section: Introductionmentioning
confidence: 99%